Assessing the performance of the radiology information systems in use in the teaching hospitals of Isfahan city based on the Great Britain’s royal college of radiologists’ guidelines - Jahanbakhsh, Maryam; Sharifi-Rad, Javad; Saghaeiannejad-Isfahani, Sakineh; Mirzaeian, Razieh (International Journal of Research in Medical Sciences, 2017)
Background: Radiology Information System (RIS) coordinates the organizational processes and administrative based on information. The present study was an attempt towards a performance assessment of the RISs used in general Isfahan hospitals. Methods: This study was descriptive cross-sectional in nature. Its statistical population consisted of the general teaching hospitals of Isfahan city (Iran). Due to the limitedness of the population of study, the sample size was the same as the population size. The data were collected using a self-designed checklist produced based on the royal college of radiologists’ guidelines, i.e. input components (13 items), process components (10 items) and output components (8 items). The researcher collected the data through observation and interview. The validity of the checklist was assessed by the health information system field’s valid authorities. Finally, the gathered data were put into SPSS 16 software and analyzed using descriptive statistics. Results: Among the RIS in the hospitals, Kashani, Isa Ibn Maryam and Nour & Ali Asghar had the highest rank for input components (mean score = 30.79%). As for process components, Al-zahra, Kashani and Isa Ibn Maryam gained the highest position (mean score = 38.9%). Finally, Al-zahra and Kashani hospitals with a mean score of 66.66% enjoyed the highest rank for output components. Conclusion: RIS must be capable of satisfying a number of requirements including satisfying the medical needs of the patients, producing the reports, image and report processing, patients’ appointment scheduling, the procedures for receiving and administrating the orders and other radiology procedures.